Breeding Cost Structure for Effective Breeding Decision in Africa - Munyaka, M.; Musundire, L.; Murtiga, S.; Odiyo, O.; Kante, M.; Mendes, T. (International Potato Center, 2023)
This report provides the results of the first costing analysis effort of the breeding pipeline “Potato East African table and processing for tropical highlands with Late Blight resistance” from the CIP program based in Kenya. The University of Queensland Breeding Costing Tool (UQ-BCT) was used to cost out the program. The current total cost of running the project is $132,029.05. The salary of the breeder was not captured in the costing. In the breakdown of operational costs, 22% is allocated to germplasm development, while the remaining 78% is attributed to germplasm evaluation. Some of the recommendations are i) encourage the optimization of the germplasm evaluation processes to increase efficiency and reduce the time and labour required, ii) work together with the procurement team to identify opportunities for negotiation and cost reduction with current suppliers, iii) enhance labour allocation and define clear roles for the breeding staff to improve trial supervision without incurring additional costs.